Women’s Collaborative Leadership in Technical and Vocational Education: A Systematic Review - Widiani Trisnaningsih; Bujang Rahman; Riswandi; Tina Yunarti; Sowiyah (Women, Education, and Social Welfare, 2026)
Women’s leadership in Technical and Vocational Education and Training (TVET) remains underexamined despite the sector’s dependence on coordinated relationships among schools, employers, government, and communities. This systematic literature review synthesizes 22 peer-reviewed studies published from 2015 to 2025 to examine women’s collaborative leadership in TVET and directly relevant educational or structurally analogous contexts. Following PRISMA 2020 procedures, records were identified through ScienceDirect and Google Scholar and analysed using inductive thematic synthesis. Four themes were identified: persistent structural and cultural barriers; individual, relational, and institutional enablers; leadership practices associated with transformational and distributed approaches; and the strategic importance of external partnerships. The evidence indicates that women’s leadership is shaped less by an inherently gendered style than by access to authority, professional networks, care-sensitive organizational arrangements, and opportunities to lead cross-boundary collaboration. Direct evidence at the intersection of women, collaborative leadership, and TVET is notably sparse. The review therefore proposes a Contextual Collaborative Leadership Framework for Women in TVET, which integrates enabling conditions, collaborative practices, boundary-spanning practices, and institutional outcomes. The framework is a research proposition requiring empirical validation.